Meningkatkan Kemampuan Motorik Halus melalui Kegiatan Finger Painting Menggunakan Pasta Ajaib Pelangi - Wuni Arum Sekar Sari; Novida Aprilina Nisa Fitri (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to improve children's fine motor skills through finger painting activities using rainbow magic paste in group B of Dharma Wanita Kindergarten 1 Babadan Ngancar, Kediri Regency, Academic Year 2021/2022. Finger painting activities using rainbow magic paste can attract children's interest in order to improve children's fine motor skills. Efforts to improve fine motor skills in this finger painting activity emphasize the coordination of hand muscles and the flexibility of children's fingers. As subjects in this study, group B of Dharma Wanita 1 Babadan Kindergarten consisted of 15 children, consisting of 5 boys and 10 girls. Researchers have carried out learning improvements which are carried out for 5 days in cycle I and continued with 5 days in cycle II considering that children's fine motor abilities have not reached the targeted level of completeness. Based on data analysis, we conclude that finger painting activities using rainbow magic paste can improve fine motor skills in group B children of Dharma Wanita I Babadan Kindergarten, Ngancar District, Kediri Regency, Academic Year 2021/2022.